Table of Content - - (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content: 1. Semantic and structural displacement in the poem "I am leaving" by the poet Rawda Al-Hajj Dr. Sara Ahmed Breamh 2. Detailed construction techniques and their effect on the directing discourse semantics: A critical reading in the samples of Nizar Qabbani’s poetry Eftekhar Salaim Mohiedain 3. The impact of Jewish Orientalism on the modern linguistic study Mr. Farid Khalil Nassar, Dr. Muhammad Ali Rabaa 4. Military Barriers Representations in Palestinian Novels after Oslo Accords: A Realistic Irony Language Dr. Hadeel Mohammed Kayyal, Prof. Nader Jomaa Qasim 5. Synthetic methods in the poetry of Saudi poet Jassim Mohammed Al-Sa Through Diwan: Three Parts of Complete Poetry Works Aryaf Faraj Alemrani